Vertical transmission of dengue - Chye, J.K.; Lim, C.T.; Ng, K.B.; Lim, J.M.; George, R.; Lam, S.K. (Oxford University Press, 1997)
Dengue, an important mosquito-borne flavivirus infection, is endemic in Southeast Asia. We describe two mothers who had acute dengue 4 and 8 days before the births of their infants. One mother had worsening of her proteinuric pregnancy-induced hypertension, liver dysfunction, and coagulopathy and required multiple transfusions of whole blood, platelets, and fresh frozen plasma. Her male infant was ill at birth, developed respiratory distress and a large uncontrollable left intracerebral hemorrhage, and died of multiorgan failure on day 6 of life. Dengue virus type 2 was isolated from the infant's blood, and IgM antibody specific to dengue virus was detected in the mother's blood. The second mother had a milder clinical course; she gave birth to a female infant who was thrombocytopenic at birth and had an uneventful hospitalization. Dengue virus type 2 was recovered from the mother's blood, and IgM antibody specific to dengue virus was detected in the infant's blood. This report highlights not only the apparently rare occurrence of vertical transmission of dengue virus in humans but also the potential risk of death for infected neonates.